PERAN EDUKASI LINGKUNGAN DALAM MENGURANGI PENCEMARAN DI DAERAH ALIRAN SUNGAI - Alif Alfiqrie, Muhammad; Firmansya, Firmansya; Sahrul, Fitra; Mukti, Cahya Krisna; Tari Sasim, Desilvi Ayu; Kumune, Roberth Richardo; Farida, Anif (Gapenas Publisher, 2025)
Watershed pollution is a serious problem that impacts public health and the environment. This activity aims to increase students' awareness of SMKN 1 Kota Sorong regarding the importance of maintaining river cleanliness and the impact of pollution on the ecosystem. The activity method consists of two stages of activities, namely the preparation and implementation stages, in which students are introduced to the concept of pollution and how to reduce it. The results of the activity show that the level of student awareness of the importance of environmental protection is still low, as indicated by the habit of littering into rivers. After the socialization, students' understanding of environmental pollution changed from 60% before the socialization to 80% after the socialization. Therefore, effective and participatory environmental education is essential to increase public awareness and involvement in maintaining water quality in watersheds for better survival.